2021
DOI: 10.3390/ncrna7030055
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Potential Biomarkers in Pituitary Adenomas

Abstract: Pituitary adenomas (PAs) are one of the most common lesions of intracranial neoplasms, occurring in approximately 15% of the general population. They are typically benign, although some adenomas show aggressive behavior, exhibiting rapid growth, drug resistance, and invasion of surrounding tissues. Despite ongoing improvements in diagnostic and therapeutic strategies, late first diagnosis is common, and patients with PAs are prone to relapse. Therefore, earlier diagnosis and prevention of recurrence are of imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…We and others have shown that microRNAs (miRNAs), small non-coding RNAs of ~22 nucleotides, may serve as reliable biomarkers of various human disorders (Keller et al, 2014;Santulli et al, 2014;Sardu et al, 2014;Novak et al, 2015;Santulli, 2015;Santulli, 2016;Cammarata et al, 2018;Slota and Booth, 2019;Dama et al, 2020;Donati et al, 2021;Jankauskas et al, 2021;Kanach et al, 2021;Kansakar et al, 2022). Therefore, the microRNAs profile could be a promising biomarker candidate…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…We and others have shown that microRNAs (miRNAs), small non-coding RNAs of ~22 nucleotides, may serve as reliable biomarkers of various human disorders (Keller et al, 2014;Santulli et al, 2014;Sardu et al, 2014;Novak et al, 2015;Santulli, 2015;Santulli, 2016;Cammarata et al, 2018;Slota and Booth, 2019;Dama et al, 2020;Donati et al, 2021;Jankauskas et al, 2021;Kanach et al, 2021;Kansakar et al, 2022). Therefore, the microRNAs profile could be a promising biomarker candidate…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Furthermore, pituitary stem cells have been identified in PitNETs, implying their crucial role in pituitary oncogenesis [18]. However, miRNAs seem to hold an essential role since they may provide new molecular targets for their diagnosis and treatment [19].…”
Section: Germline/ Somaticmentioning
confidence: 99%
“…Among the abundant DE ncRNAs, miRNAs are the most widely studied. We discuss the role of miRNAs in different PA subtypes in tissues, biofluids, and cell-free environments [ 17 , 18 , 19 , 20 , 37 ]. miRNAs inhibit the expression of target genes at the post-transcriptional level by pairing with the 3′-UTR of mRNA ( Figure 1 ); thus, miRNAs are involved in various pathological and physiological processes by playing a negative role in cell proliferation, differentiation, metabolism, and apoptosis.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%